Pharmacological evaluation of the anxiolytic-like effects of Lippia graveolens and bioactive compounds - María Eva González-Trujano; Laura Yunuen Hernández-Sánchez; Verónica Muñoz Ocotero; Alejandro Dorazco-González; Patricia Guevara Fefer; Eva Aguirre-Hernández (Taylor & Francis Group, 2017)
Context: Lippia species (Verbenaceae) are widely used in Latin America and Africa as folk medicine for their tranquilizing properties. Objective: To evaluate the anxiolytic-like effects and safety of Lippia graveolens Kunth. by exploring its aqueous and organic leaf extracts and identifying the responsible chemical constituents. Material and methods: Aqueous and organic extracts (hexane, ethyl acetate and methanol) were pharmacologically evaluated at several doses. Chemical constituents were identified using MS, NMR and GC-MS analysis. The isolated compounds (3 mg/kg, i.p.), extracts (1, 3, 10 and 30 mg/kg, i.p.), and the reference drug diazepam (0.1 mg/kg, i.p.) were assessed in CD-1 mice using experimental behavioural models: open-field, cylinder, hole-board, plus-maze and sodium pentobarbital-induced hypnosis, as well as their acute toxicity (LD50). Results: After administration of the extracts and bioactive compounds, a significant anxiolytic-like response from 1 mg/kg, i.p. was observed, resembling the effect of diazepam. Major presence of thymol (33.40%) was observed in the hexane extract; whereas for the first time in this species a p-cymene + thymol mixture (9.78%), naringenin (0.18%) and cirsimaritin (1.16%) were obtained as bioactive constituents of the ethyl acetate crude extract. Acute toxicity was calculated to be LD50 = 1000 mg/kg for the crude hexane extract, lower in comparison to the other extracts analyzed (LD50 > 2000 mg/kg). Discussion and conclusion: Our results suggest that L. graveolens exerts anxiolytic-like activity involving many kinds of constituents, mainly of the terpenoid and flavonoid nature. These results reinforce the potential use of this species in the therapy of anxiety.